Gambaran Perilaku Pemilik Anjing Lokal terhadap Pencegahan Rabies - Wiradani, Ni Luh Kade (Jurnal Skala Husada : The Journal of Health, 2023)
ABSTRACT Background. The number of human death because of rabies in Bali Province between 2008 and 2011 was 133 people. The rabies cases were high because many local dog owners did not take care of their dog properly.Aim. To identify the behavior of local dog owners towards rabies prevention.Methods. The study was a descriptive, cross-sectional study. The samples of this research were 244 respondents which were drawn through consecutive sampling. Data were collected by using questionnaires and analyzed descriptively.Results. On the category of rabies prevention, 44.3% of respondents had good behavior; 33.6% of respondents had moderate behavior and 22.1% of respondents had poor behavior. On the category of behavior in caring for the dogs, 29.1% of respondents had good behavior; 34.8% of respondents had moderate behavior and 36.1% of respondents had poor behavior. On the category of dog’s vaccination 61.5% of respondents had good behavior; 22.5% of respondents had moderate behavior and 16% of respondents had poor behavior.Conclusion. Local dog owners are expected to maintain their good behavior regarding dog’s vaccination and improve their behavior in caring for the dog by attending the socialization program from Animal Husbandry DepartmentKeywords: behavior, local dog owners, prevention, rabies